14C-based ΔffCO2 estimates for Heidelberg and OPE and input data for the Rhine Valley ffCO2 inversion (2019-2020) - Maier, Fabian; Levin, Ingeborg; Hammer, Samuel; Conil, Sébastien; Preunkert, Susanne (Universität, 2023)
These data files show the Δ14CO2, CO2 and CO measurements as well as the 14C-based ΔffCO2 estimates of the flask samples collected in Heidelberg (HEI, 2019-2020) and at the ICOS site Observatoire pérenne de l'environnement (OPE, Sep. 2020 - Mar. 2021). Moreover, modelled ΔffCO2 and ΔCO concentrations based on the Stochastic Time-Inverted Lagrangian Transport (STILT) model and the Netherlands Organization for Applied Scientific Research (TNO) emissions are given for the respective flask hours. These data are used to compare flask-based with inventory-based ΔCO/ΔffCO2 ratios (Maier et al., 2023a). For Heidelberg, also ΔCO-based ΔffCO2 estimates are presented for the afternoon hours in 2019 and 2020. The afternoon 14C- and ΔCO-based ΔffCO2 estimates from Heidelberg are used as observational constraint in the ffCO2 inversion performed in the Rhine Valley (Maier et al., 2023b).